GOVERNMENT EXPROPRIATION COMPENSATION AND HOUSEHOLD ENERGY POVERTY: IMPLICATIONS FOR SUSTAINABLE DEVELOPMENT IN CHINA - Shujing Zhang; Zhaoyuan Chen (PEOPLE: International Journal of Social Sciences, 2026)
Energy poverty remains a persistent challenge in developing countries and poses an important constraint on achieving sustainable development. Against this backdrop, this study examines how government expropriation compensation influences household energy poverty in China, focusing on land expropriation compensation and housing demolition compensation. Using nationally representative data from the China Family Panel Studies covering 2014–2022 and a difference-in-differences framework, the study identifies the causal effects of both types of compensation on alleviating energy poverty.The results show that land expropriation compensation and housing demolition compensation significantly reduce household energy poverty, with stronger effects observed for land compensation. The impacts are more pronounced among low-income, agricultural, and central-western households. Mechanism analysis reveals that compensation mitigates energy poverty primarily through increasing household income, improving housing conditions, and enhancing access to modern energy facilities.These findings suggest that compensation policies can contribute to reducing energy inequality and supporting broader sustainable development objectives by improving access to basic energy services.